THE ALGORITHM FOR CALCULATING THE PROBABILITY OF ERROR IN FADING RADIO CHANNELS USING THE METHOD OF ROTATION - Vladimir Petrovich Pashincev; Alexander Fedorovich Chipiga; Maria Anatolevna Lapina; Ilya Evgenievich Hohlov (Вестник Северо-Кавказского федерального университета)
The algorithm of calculating the dependence of the error probability of diversity reception of the signa-to-noise ratio and correlation coefficient rayleigh fading signals at high multiplicity of spacing.